Secret agencies : U.S. intelligence in a hostile world - Johnson, Loch K., 1942- (Yale University Press, 1996)
"Secret agencies have the capacity not only to safeguard democracy but also to subvert it ... As such, they deserve both our support and our scrutiny."--Jacket